Análise comparativa de lojas de departamentos virtuais no Brasil - Bomfim, Patrícia Portella (2002)
The present dissertation care is focused on the study of the virtual department stores¿ behavior, through the analysis of following parameters: site design and digital interface with the user, advertising and promotion, logistics, assistance to client, business models, security policies, loyalty programs, payment options and moulds policies. This study will focalizes the department stores which commercializes, on-line, more than one product category produced by third party ¿ so much the ones that chooses the Internet as its only sales channel (e.g.: submarino.com), as much as those that uses Web as a complementary sales channel (e.g.: americanas.com).